Medicīniska rakstura piespiedu līdzekļu piemērošana - Raudiva, Ilva (Latvijas Universitāte, 2013)
Bakalaura darba tēma ir medicīniska rakstura piespiedu līdzekļu piemērošana. Darba ietvaros tiek veikts salīdzinājumus starp Latvijas PSR Kriminālprocesa kodeksu un Kriminālrpocesa likumu ar mērķi konstatēt vai ir bijusi attīstība medicīniska rakstura piespiedu līdzekļu piemērošanā. Otrajā nodaļā autore pievēršas medicīniska rakstura piespiedu līdzekļu jēdziena izpratnei, lai iegūt skaidrību, kādām personām ir piemērojami šie medicīniskie piespiedu līdzekļi. Autore apskata kriminālprocesa īpatnības nosakot medicīniska rakstura piespiedu līdzekļus. Šajā darbā tiek norādīts uz procesuālajām atšķirībām, kādas pastāv starp nepieskaitāmām un ierobežoti pieskaitāmām personām.

The theme of degree work is coercive medical measures. Author has chosen to compare two laws – Latvian PSR Code of Criminal Procedure and Law of Criminal Procedure in order to find out the development of regulation of coercive medical measures in Latvia. Second part of the work contains reaserch about concept of coercive medical measures. Therefore this par of the work is about those persons whom coercive medical measures are applicable and about the role of coercive medical measures in criminal proceeding. In the third chapter of the work the attention is focused on conditions which affect the choice of coercive medical measures, such as, forensic psychiatric expertise. The last part of the work is about the proceeding in criminal procedure acording to wich the coercive medical measures are applied to psychicaly ill persons.
Coercive medical measures
Keywords: Juridiskā zinātne